Foreign trade regimes and economic development : the Philippines - Baldwin, Robert E.; National Bureau of Economic Research (New York : National Bureau of Economic Research : distributed by Columbia University Press, 1975)
This volume is one of a series resulting from the research project on Exchange Control, Liberalization and Economic Development sponsored by the National Bureu of Economic Research.
A special conference series on Foreign Trade Regimes and Economic Development. Volume V.
Includes bibliographical references and index.
osa 24/01/2019
Loans
Keywords: Economic history; International trade